Space-time modulation and coding over transmit correlated fading channels. - Godbout, M. (IEEE Transactions on wireless communications)
Multi-dimensional space-time modulation schemes can be classified by the manner in which signal dimensions are shared among transmit antennas. In aggregate transmit antenna (ATA) systems, a generalization of Tarokh, Seshadri, Calderbank's (TSC) approach, there is total sharing of dimensions. In orthogonal transmit antenna (OTA) systems, a generalization of many traditional diversity schemes, there is no sharing of dimensions. In partially orthogonal transmit antennas (POTA), a combination of ATA with OTA, subsets of available dimensions are shared by subsets of transmit antennas. This letter considers such coded schemes for spatially correlated fading channels. Over strongly transmit correlated channels, in addition to coding and diversity gains, ATA and POTA can harvest a transmit beamforming-like gain. This letter presents a scheme, POTARep, designed to provide beamforming-like gain as well as diversity and coding gains, yielding improved performance over a highly transmit correlated channel.